THE ROLE OF ALTERITY AND OF THE DIGITAL MEDIA IN OUTLINING OF THE POSTMODERN INDIVIDUAL’S IDENTITY - Raluca Marinela SILAGHI (Studia Universitatis Babeș-Bolyai. Philosophia, 2015)
The Role of Alterity and of the Digital Media in Outlining of the Postmodern Individual’s Identity. The postmodern individual forms his identity, his self-image and self-perception not only through self-reflection or through reference to his own convictions, his own system of values and principles. The construction of the self-image is dependent upon social recognition and on the messages transmitted from the other, during the interaction between them. The relevance of the other for the process of defining one’s self-identity leads ultimately to dependence on mass-media, which offers to “gratuitously” help the individual in obtaining the social recognition that he aspires to, by constituting and reinventing himself in such a manner as to distinguish himself through superiority from the masses. Such dependence on mass-media leads to the alienation of the individual from his self, to his forming a subservient relationship towards trendy cultural models, opinion leaders or group opinions, dispensing with the individual’s autonomy and capacity of critical reflection on the information he is presented with.